Modelagem dos conceitos associados à notificação compulsória de maus tratos contra crianças e adolescentes - Santos, Michele Mariana Vieira Ferreira (2014)
ntroduction: According to WHO data, the violence committed against children and adolescents is of such standard that has already become a public health problem. In ensuring the rights of this age group, the NHS recommends priority attention blaming health professionals and others in reporting suspected abuse suffered by them. While this in practice, we face several difficulties regarding the reporting of violence by these professionals. Objective: Modeling concepts of mandatory reporting of abuse record as a basis for the development of a computerized monitoring system of its occurrence. Materials and Methods: The notification form has been pre-selected for the modeling of concepts to be included in a computerized detection of abuse against children and adolescents. The modeling of the knowledge used is based on the principles of multilevel modeling of health information systems. Results: The mapping of data from the Notification Form with openEHR archetypes model found 27 matches for a total of 57 items, of which 22 were considered total and partial other 05. In the "Data of Violence", none of the items "If violence occurred, what kind" and "If penetration has occurred, what type" found corresponding archetypes available in Clinical Knowledge Modeler (CKM), we chose to model this group concepts into an archetype. Conclusions: The modeling concepts of Record may assist in future in computer-aided diagnosis and provide us with an information filed in how professionals can identify such cases and intervene in time protecting and preserving children and adolescents from this type of violence.